Antenatal Rolling Back Massage Combined with Breast Care: Effect on Postpartum Breast Milk Output - Andi Ria Metasari; Nursari Abdul Syukur; Parellangi; Nurul Rahmadini Hakim; Heni Suryani; Rahmawati Wahyuni; Jasmawati; Diah Ulfa Hidayati; Ega Ersya Urnia; Dewi Rinda Astuti (Borneo Scientific Publishing, 2026)
Breastfeeding problems often emerge during the antenatal period, with many mothers experiencing delayed or insufficient breast milk output during the first to third days postpartum. Inadequate breast care and the absence of rolling back massage during pregnancy are known to negatively affect breastfeeding outcomes. This study aimed to determine the effect of combining rolling back massage with breast care during the third trimester of pregnancy on postpartum breast milk output. A quasi-experimental study with a two-group posttest-only control group design was conducted at Klinik Aminah Amin Rianta 1 from April 1 to May 31, 2024. A total of 36 third-trimester pregnant women (≥36 weeks’ gestation) were recruited using accidental sampling (18 per group). The treatment group received rolling back massage (along the spine from the cervical region to costa 5–6, twice during the third trimester) in addition to breast care, while the control group received breast care only. Breast milk output was assessed on the first to third postpartum day and categorized dichotomously as ‘present’ or ‘absent’ using a standardized observation checklist. Fisher’s Exact Test was used for analysis. The treatment group demonstrated markedly higher breast milk output (94.4%) compared with the control group (61.1%). A statistically significant effect was confirmed (ρ = 0.041, p < α = 0.05). The combination of rolling back massage and breast care during the third trimester significantly improves postpartum breast milk output. Integration of both interventions into antenatal care is recommended, with the caveat that future randomized studies with larger samples are needed to confirm generalizability.